Fiscal and monetary rules for a currency union - Andrea Ferrero (European Central Bank (ECB), 2005)
This paper addresses the question of the joint conduct of fiscal and monetary policy in a currency union. The problem is studied using a two-country DSGE framework with staggered price setting, monopolistic competition in the goods market, distortionary taxation and nominal debt. The two countries form a currency union but retain fiscal policy independence. The policy problem can be cast in terms of a tractable linear-quadratic setup. The stabilization properties and the welfare implications of the optimal commitment plan are compared with the outcome obtained under simple implementable rules. The central result is that fiscal policy plays a key role to smooth appropriately the impact of idiosyncratic exogenous shocks. Fiscal rules that respond to a measure of real activity have the potential to approximate accurately the optimal plan and lead to large welfare gains as compared to balanced budget rules. Monetary policy shall focus on maintaining price stability.
Keywords: E63; F33; F42; 330; Currency union; Flexibility; Optimal Policy; Welfare; Finanzpolitik; Geldpolitik; Stabilisierungspolitik; Theorie; Simulation; Währungsunion; Eurozone; EU-Staaten